About the Stylistic Adaptation of Turkish Loanwords in Macedonian - Keti Miteva-Markovikj (European Scientific Journal, ESJ, 2018)
In a long period of their developmental paths, the Balkan languages have been in continuous contact with each other and have had mutual interference, by which their linguistic structures in a large extent have approximated with the aim of a better intelligibility among the speakers of those languages. Within the lexis, the Turkish language played a dominant role primarily because of the 500-year reign of the Ottoman Empire. All the Balkan languages, especially the Macedonian language, enriched their lexical fund with a large number of Turkish loanwords from all domains of human life. Some of the words made one's way into the domain of archaic and dialectical lexis, however one group of words remained functional in contemporary expressions. Within this text, several Turkish lexical loanwords in the Macedonian language are scrutinized, as well as by analyzing examples, their shift in the stylistic register and increased expressiveness within the contemporary Macedonian language are analyzed. The analyzed examples are from author's personal corpora and are collected through the oral communication, print and digital media. Selected examples will serve to analyze and to prove semantic and stylistic shift in the spoken register of the contemporary Macedonian language.